The Pepper CaOSR1 Protein Regulates the Osmotic Stress Response via Abscisic Acid Signaling - Park, Chanmi; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2016)
Plants are sessile organisms, and their growth and development is detrimentally affected by environmental stresses such as drought and high salinity. Defense mechanisms are tightly regulated and complex processes, which respond to changing environmental conditions; however, the precise mechanisms that function under adverse conditions remain unclear. Here, we report the identification and functional characterization of the CaOSR1 gene, which functions in the defense response to abiotic stress. We found that CaOSR1 gene expression in pepper leaves was up-regulated after exposure to abscisic acid (ABA), drought, and high salinity. In addition, we demonstrated that the fusion protein of CaOSR1 with green fluorescent protein (GFP) is localized in the nucleus. We used CaOSR1-silenced pepper plants and CaOSR1-OX-overexpressing (OX) transgenic Arabidopsis plants to show that the CaOSR1 protein regulates the osmotic stress response. CaOSR1-silenced pepper plants showed increased drought susceptibility, and this was accompanied by a high transpiration rate. CaOSR1-OX plants displayed phenotypes that were hypersensitive to ABA and hyposensitive to osmotic stress, during the seed germination and seedling growth stages; furthermore, these plants exhibited enhanced drought tolerance at the adult stage, and this was characterized by higher leaf temperatures and smaller stomatal apertures because of ABA hypersensitivity. Taken together, our data indicate that CaOSR1 positively regulates osmotic stress tolerance via ABA-mediated cell signaling. These findings suggest an involvement of a novel protein in ABA and osmotic stress signalings in plants.